Abdominal type B vs. type C radical hysterectomy in early-stage cervical cancer: A matched single center cohort report - Wang, Lu; Liu, Ping; Duan, Hui; Li, Pengfei; Su, Guidong; Li, Weili; Liang, Cong; Chen, Chunlin (Frontiers in Surgery, 2023)
Objective: To compare survival outcomes of type B radical hysterectomy (RH) and type C RH in patients with early-stage cervical cancer. Methods: We retrospectively identified continuous cervical cancer patients with FIGO stage IA2-IB2 and IIA1 who underwent either type B RH (n=278) or type C RH (n=148) performed by the same group of surgeons between 2009 and 2018. Propensity score matching was carried out to minimize selection biases. Intraoperative photographs, immediate postoperative questionnaire and specimen measurements were used to accurately determine the extensive of surgery. We further narrowed the study population to patients with specific histological subtypes and patients with deep stromal invasion. Results: The median follow-up period was 42.41±24.60 months. After adjusting, no differences in the 5-year overall survival (OS) and disease-free survival (DFS) were found between the type B group and the type C group (OS: 87.8% vs. 89.4%, P=0.814; DFS: 84.9% vs. 85.6%, P=0.898). In further analysis of patients with squamous-cell carcinoma, adenocarcinoma, adenosquamous carcinoma, similar 5-year OS and DFS rates were found between two groups (OS: 88.7% vs. 97.1%, P=0.250; DFS: 84.7% vs. 92.3%, P=0.541). Consistent results were found in patients with deep stromal invasion (OS: 81.8% vs. 100%, P=0.144; DFS: 82.8% vs. 100%, P=0.128). Conclusions: Type B RH could be used to treat FIGO stage IA2-IB2 and IIA1 cervical cancer to get equivalent 5-year OS and DFS. Further randomized controlled trials are warranted.